Genotype by environment interaction and stability analyses of grain yield of selected maize (Zea mays L.) genotypes in eastern and central Sudan - A. Ibrahim, Hashim; S. Ibrahim, Abu Elhassan; A. Ali, Khalfala (Gezira Journal of Agricultural Science, 2021)
In this study, 22 open pollinated maize genotypes introduced from International Maize and Wheat Improvement Center (CIMMYT) and International Institute of Tropical Agriculture (IITA) plus two local checks (Var113, Hudieba-2) were evaluated over two seasons (2017 and 2018) and four locations, viz. New Halfa, Kassala, Gezira and Elsuki Research Station farms of the Agricultural Research Corporation (ARC) of the Sudan. The objectives of this study were to determine magnitude of G x E interaction and identify high yielding and stable genotypes under different environments. Treatments were arranged in a randomized complete block design with three replicates. Combined analysis of variance revealed highly significant (P<0.01) variation among environment, genotype, and genotype by environment interaction (GEI). This is an indication of inconsistency of genotypes in response to changing environment, the high influence of environment on yield performance among the maize genotypes and, also, the significant effect of environments indicated that the testing environments were significantly different from each other in yielding potential expression. AMMI analysis of variance for grain yield showed the environment contribution by (24.06%) of the total yield variation and genotypes explained only (9.84%) of the variation. Also, substantial percentage of G x E interaction sum of squares, explained by G x E (50.41%) followed by IPCAI (19.22%) and IPCA2 (15.52%) of the variation. Based on grain yield potential and statistical stability analyses, i.e. Eberhart and Russel model (1966) as well as the additive main effect and multiplicative interaction (AMMI) analysis, revealed that, the genotypes TZBR Eld-4-WC1, BR9922-DMRSR,TZBR Comp1-w, TZBR Comp1-Y and TZBR YPOP STRCY were  recommended for the high yielding favourable supplementary irrigation condition (over 3000 kg/ha) of New Halfa, Gezira and Elsuki while the genotypes TZBREld-3C5, TZBREld-4-WC1, HYDERAB, 97502 (RE) and ECA STRIGOFE-153 were recommended for the unfavourable low yielding (less than 1500 kg/ha) rainfed condition of Kassala.